Low-voltage ride-through scheme for distributed generation inverters using a modified current reference strategy - Wen, Fankai (2024)
The growing number of distributed generations (DGs) has shifted the power supply to be more flexible and reliable. Meanwhile, for the stability of the power grid, the increasing integration demands a robust fault ride-through (FRT) ability when the unbalanced sag occurs in the grid operation, namely low-voltage ride-through (LVRT). During an unbalanced sag, the oscillation in the active and reactive power, the distorted and unbalanced current are the main significant detriments. Several current reference strategies have been developed to mitigate these adverse effects. However, the standard approach prioritizes compensation for one objective entirely, typically the sag, at the expense of leaving another objective unaddressed i.e. constant powers, balanced current, or harmonic distortion. To accomplish the characteristics of different current reference strategies, this paper modifies the current reference to achieve two control variables. Besides, to accurately boost the voltage at the point of common coupling, the reactive power compensation reference is proposed according to the power transfer equation. A model predictive control (MPC) controller is designed to deliver a given power by making the current follow the reference. The simulation results show that the proposed LVRT scheme achieves at the PCC voltage a more accurate and larger boost and the modified current strategy can decouple the traditional strategies.